IMPACT OF COVID-19 ON PERCEPTION OF CULTURAL ECOSYSTEM SERVICES IN BALATHIRUTHI ISLAND IN KERALA - Kongath, Muhammed Fazal; Agrawal, Sarita (International Journal of Research -GRANTHAALAYAH, 2022)
Maadaath Thiruthi island (CP Thiruthi) in Balathiruthi is near Kadalundi estuary in Malappuram district. It is rich in its biodiversity with estuary, mangroves, and naturally picturesque inland. The place is a treasure of all categories of cultural ecosystem services. Perception of cultural ecosystem services in homeland is bliss for its local people. But people of this area cannot perceive it much due to many problems. One of the major problems is the issue of their livelihood options. This started after the termination of traditional industry of coir retting from the region. This became more severe due to COVID-19. These problems have affected its natives badly. This study attempts to measure the impact of COVID-19 on the perception of local people in accessing cultural ecosystem services in the study area. The study is based on primary survey of them using random sampling. The data were focused on Cultural Ecosystem Services, impact of COVID-19 and livelihood problems.